Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Motivasi Belajar Siswa Pada Mata pelajaran SKI - Fauziah, Hapsah; Fadilah, Silvi Dinar (STAI Al-Musaddadiyah Garut, 2025)
Learning motivation is the overall psychic driving force within a person that causes learning activities and provides direction to those learning activities in order to achieve a goal. Based on that, learning motivation is one of the determining elements of student learning outcomes. However, in reality there are motivational problems that occur that indicate extrinsic motivation problems. This can be seen from the data obtained from the research location regarding the lack of appreciation in learning, the lack of interesting activities in learning and the lack of a conducive learning environment. The impact that occurs if students do not have motivation will be that there will be no goals and organized behavior. There are many things that can be done to improve student learning motivation, one of which is by implementing a cooperative learning model of the think pair share type which can create effective and enjoyable learning, is able to provide motivation, and can improve learning outcomes. The purpose of this study was to describe the effect of implementing a cooperative learning model of the think pair share type on student learning motivation in the subject of Islamic Cultural History. Thus, to determine the effect of implementing a cooperative learning model of the think pair share type (Variable X), with student learning motivation in the subject of Islamic Cultural History (Variable Y). This type of research uses quantitative with descriptive methods. The data collection techniques are by means of questionnaires, observations, interviews and documentation studies. The subjects in this study were students of grades VII and VIII at MTs Darul Asyiqin Banyuresmi Garut, namely 87 students. The results of the study, Fcount> Ftable, namely 57.366> 3.95, then the decision taken is H0 is rejected, then Ha is accepted. Based on the calculation of the coefficient of determination, it shows that there is an influence of the application of the think pair share type cooperative learning model on student learning motivation by 40.3% and the remaining 59.7% is influenced by other factors not included in this study. Keywords: Think Pair Share Type Cooperative Learning Model; Student Learning Motivation; History of Islamic Culture.